Some thoughts on the axiology and constitutionalization of the World Trade Organization - Ziemblicki, Bartosz (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The rationale for the existence of the WTO is the assumption that international trade is beneficial to all parties. The theoretical justification for this assumption is the theory of comparative advantage. The WTO may also be credited with a contribution to peacekeeping and has strong doctrinal and philosophical foundations.The WTO is often accused of a bias towards exporters and failure to provide appropriate protection to other market participants. Other conflicting powers within the Organization are the supporters of free trade and fair trades. The third doctrinal tension is between the legislative and judicial powers. The Ministerial Conferences are ever more unable to make decisions and reform the WTO. At the same time a very effective dispute settlement mechanism is beginning to fill the gaps in legal texts.The WTO is often presented as an example of the ongoing process of constitutionalization of international law. The concept is difficult to define and each scholar distinguishes different characteristics. It is arguable whether the WTO is undergoing the process of constitutionalization and also whether it can be perceived as a self-contained régime. The contribution of the WTO to global governance in comparison to that of the GATT is another issue under discussion.
Keywords: Światowa Organizacja Handlu (WTO); handel